KERJASAMA INDONESIA-KOREA SELATAN DALAM MENGIMPLEMENTASIKAN KEAMANAN CYBER DENGAN STUDI KASUS CYBERPORN - Novel, Elin Konstantia; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Pornography has become one of the complicated problems in law enforcement. It is because of the spread which is so massive, so it is difficult to be overcome. Pornography, along with the existence of the internet, is another challenge for the law holders to eliminate it as a cyber porn crime (Pornography in internet) which gives the massive impact. In the context of a crime, cyber porn can be categorized as one of the cyber crimes.The perspective is Constructivism because cyberporn is a result from the construction of mind of human being and the impact of technology. The teory in this research is human security and written by Allan Collins. The level analysis is nation state and written by Charles W Kegley Jr dan Eugene R Wittkopf. The data is obtained through primary data and secunder data such as, book, journal, magazine, newspaper and website.This research is based on the high crime of cybercrime in the world especially in Indonesia, making South Korea and Indonesia cooperate in developing cyber porn. This study aims to find out how the cooperation of Korea International Cooperation Agency (KOICA) and the Government of Indonesia in the development of cyber security against cyber porn. The results of this study show the cooperation process conducted through cooperation between Korea International Cooperation Agency (KOICA) and the Government of Indonesia in the development of cyber security that is printing Human Resources (HR) in cyber security, security against malware and exchange of information between the two countries in preventing the occurrence of cyber Threats.Key words: Cyberporn, KOICA-ITB, Cybersecurity, Human security,